2017
DOI: 10.1183/13993003.01740-2017
|View full text |Cite
|
Sign up to set email alerts
|

Two-year follow-up after endobronchial coil treatment in emphysema: results from the REVOLENS study

Abstract: Severe emphysema is a difficult to treat condition with limited efficacy of currently available treatments. Endobronchial coil treatment (ECT) is a minimally invasive endobronchial treatment which consists of placing shape-memory nitinol coils in emphysematous lobes to enhance lung recoil and reduce lung hyperinflation at rest and during exercise [1, 2]. Randomised studies demonstrated an improvement in exercise capacity, lung function and quality of life, and showed an acceptable safety profile at 1 year [3][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In addition, the fewer number of donor lungs available can be used for transplantation in those with more serious diseases. BLVR coil therapy has been increasingly used in recent years, and studies have shown improvement in 6-MWT, PFT parameters, and quality of life with this treatment (11,12,(18)(19)(20)(21)(22)(23)(24)(25)(26). This treatment method is an alternative and effective treatment option for emphysema patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the fewer number of donor lungs available can be used for transplantation in those with more serious diseases. BLVR coil therapy has been increasingly used in recent years, and studies have shown improvement in 6-MWT, PFT parameters, and quality of life with this treatment (11,12,(18)(19)(20)(21)(22)(23)(24)(25)(26). This treatment method is an alternative and effective treatment option for emphysema patients.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment method is an alternative and effective treatment option for emphysema patients. The most recent and largest studies are the REVOLENS study and the RENEW study (11,24). In these studies, 50 patients and 158 patients were treated with BLVR coil therapy, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2-year followup confirms durable benefits in volume reduction, QoL, and safety profile. 56 RENEW in 2016 is the largest multicenter, randomized controlled, assessor-blinded, study of 315 patients with severe emphysema (heterogeneous and homogeneous using a semiquantitative visual assessment) and hyperinflation comparing bilobar coil implantation (n ¼ 158) to SoC (n ¼ 157). 57 LVRCs were implanted in one lobe of each lung in sequential operations.…”
Section: Clinical Datamentioning
confidence: 99%